Modelling written communication a new systems approach to modelling in the social sciences - Pratt, Deirdre (Methodos series, 2011)
This book offers an alternative view to current postmodern approaches to composition. It takes a critical realist stance to arrive at the 'essence' of written communication with the aim of informing a practical application: a computerised writing tutor. Following Robert Franck's seminal work on modelling, a theoretical model of writing was first formulated, consisting of an architecture of functions which constitute the prerequisites for effective communication. Next, an applied model - a composing algorithm with an input option - was developed, showing composing to be a systemic social process with intra- and extra-systemic variation. The algorithm provided the design template for a writing tutor program which models for the learner both the systemic and the socially situated nature of writing. This book establishes composing as a communicative interaction, and shows the essential dynamism of writing, while offering an exemplar of a systems approach to modelling in the social sciences